Analysis of Relationship between the Performance and Efficiency Based on CCR And BCC Models in the Iranian Insurance Industry: Tobit's Approach - Javad Montazeri; Reza Yazdani; Meysam Kaviani (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: This paper aims to assess the efficiency of existing companies in Iran's insurance industry and its relationship with essential profitability ratios. Therefore, with the help of input-axis and output-axis approaches, the performance of the companies was investigated, and the relationship between profitability and efficiency was studied using Tobit's regression model. Methodology: To achieve the answer to the above question, we selected 14 insurance companies in the capital market of Tehran as statistical samples. The data collected in 10 years between 2012 and 2018 have been considered. The hypothesis test has been performed by considering the dependent variable of dividends in different forms through Tobit and logit regression analysis. Findings: The results confirm that during the six years (2011 to 2016), the return on assets with a calculated efficiency is positively correlated with the input-oriented approach and has a negative relationship with the output-oriented approach. The results also show that the return on equity has no significant relationship with the two performance approaches. Originality/Value: In this study, considering the ratio of total liabilities, equity, and assets as input variables and income and sales, premium, and net profit as output variables, the ability to aggregate these items and translate them into one It has a single criterion called "efficiency" with two approaches.